2000
DOI: 10.1046/j.1365-2508.2000.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of operative laparoscopy

Abstract: Objective  To assess the incidence and type of laparoscopic complications. Design  A series of 1649 operative laparoscopies were reviewed in a retrospective study of patient records. Setting  A tertiary care university hospital. Interventions  Operative laparoscopy including minor procedures (minimal adhesiolysis, destruction of minimal endometriosis foci, ovarian biopsy, ovarian puncture, tubal sterilization); major laparoscopic surgery (extended adhesiolysis, tuboplasties, uterine suspension, treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 7 publications
(16 reference statements)
2
20
0
2
Order By: Relevance
“…It was also noted that adhesions from previous surgery, pelvic infections and endometriosis predispose to injuries (14). Miranda et al in 2000 reported one major vessel injury, two intestinal injuries (0.2%), one anaesthetic complication and two urinary tract injuries (0.2%) in a series of 1649 operative laparoscopies (15).…”
Section: Resultsmentioning
confidence: 99%
“…It was also noted that adhesions from previous surgery, pelvic infections and endometriosis predispose to injuries (14). Miranda et al in 2000 reported one major vessel injury, two intestinal injuries (0.2%), one anaesthetic complication and two urinary tract injuries (0.2%) in a series of 1649 operative laparoscopies (15).…”
Section: Resultsmentioning
confidence: 99%
“…The median interval for the TLH group was 13 days, and for the TAH and VH groups, it was 11 days. Of the few reported cases in literature, the time interval varied from 3 to 18 days [1,2,4].…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall incidence of secondary hemorrhage is low, gynecologists do come across secondary hemorrhage of varying degrees of severity [1]. There are few studies which show the overall incidence of hemorrhage of 0.2-2 % after hysterectomy which includes reactionary and secondary hemorrhage [1][2][3][4]. Our centre has been performing laparoscopic hysterectomies since 1994, and we encounter one or two cases of secondary hemorrhage per year in the second or third postoperative week which necessitates hospitalization and active treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Il a été rapporté par la plupart des études que sa morbidité per-et postopératoire reste faible avec un taux de complications de 0,27 à 1,97 % [2,3,5,8,[11][12][13][14]. Ce taux a été un peu plus élevé dans notre série : 2,46 % (Tableau 4).…”
Section: Résultatsunclassified
“…Les complications mineures étaient de 1,8 % dans notre série et les majeures de 0,66 %. Ce dernier taux reste élevé par rapport à celui des grandes séries [2,13,14]. Cela pourrait s'expliquer par le fait que nos patientes ont très souvent des adhérences (78,16 %), ce qui majore le risque de complication aussi bien lors de l'installation de la coelioscopie que pendant le geste opératoire.…”
Section: Résultatsunclassified